Development of an Android-Based Plant Care Simulation Game Using the Finite State Machine Method and Time-Based Growth Algorithm - M Rayyan Al Fariz Prasetya; Al-Khowarizmi (Tsabit Journal of Computer Science, 2026)
The advancement of digital technology has created new opportunities for delivering educational content in an interactive manner, particularly on the topic of plant growth cycles, which are often difficult to understand theoretically through traditional learning methods. This study aims to develop an Android-based plant care simulation game utilizing the Finite State Machine (FSM) method and the Time-Based Growth algorithm, which can serve as an alternative medium for both entertainment and education. The FSM method is implemented to manage structured transitions between plant growth phases, while the Time-Based Growth algorithm regulates the duration of each growth stage based on time and in-game interactions, such as watering and fertilizing. The development process follows the Multimedia Development Life Cycle (MDLC), which consists of the stages of concept, design, material collecting, assembly, testing, and distribution. The implementation results indicate that the system is capable of dynamically representing the plant growth cycle through mechanisms involving plant health (HP), water levels, a delay-death phase, and growth acceleration through fertilizer usage. Based on testing results, the application functions according to the design specifications and provides an interactive and engaging learning experience.